Freestanding multi-gate IZO-based neuromorphic transistors on composite electrolyte membranes. (29th December 2021) - Wang, Xiangjing; Zhu, Li; Chen, Chunsheng; Mao, Huiwu; Zhu, Yixin; Zhu, Ying; Yang, Yang; Wan, Changjin; Wan, Qing
Abstract: Brain-inspired neuromorphic computing would bring a breakthrough to the classical computing paradigm through its massive parallelism and potential low power consumption advantages. Introduction of flexibility may bring vitality to this area by expanding its application areas to such as wearable and implantable electronics. At present, the development of flexible neuromorphic devices makes it a choice with wide prospect for next-generation wearable artificial neuromorphic computing. In this study, a freestanding graphene oxide/polyvinyl alcohol composite solid electrolyte membrane is utilized as the gate dielectric and support material, and indium-zinc-oxide (IZO) neuromorphic transistors are fabricated on such membrane. Based on the in-plane gate modulation, many key synaptic plasticity behaviors have been successfully emulated, including excitatory postsynaptic current, paired-pulse facilitation, high-pass filtering, and spatiotemporal signal processing. Moreover, transition of the spiking logic and the superlinear and sublinear dendritic integration function are realized. Our results indicate that these freestanding IZO-based neuromorphic transistors may of great significance for future flexible anthropomorphic robots, wearable bionic perception.